2017
DOI: 10.21511/bbs.12(3).2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of liquidity risk in Islamic banks

Abstract: This research analyzes the determinants of liquidity risk in Islamic banks by using a comprehensive model that incorporates several variables that impact the liquidity of Islamic banks. A panel data analysis is conducted on a sample of 42 Islamic banks from 15 countries between 2007 and 2014. The results show a negative correlation between liquidity risk and cash ratio, as the cash balance can be used to meet any demands for liquidity from the bank's customers. There is negative correlation between liquidity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 8 publications
8
28
0
8
Order By: Relevance
“…Some previous studies present that among the crucial factors affecting NPL are economic growth, which negatively correlates with the NPL and NPF. Similar studies have found that macroeconomic factors have a significant relationship with NPL and NPF (Alzoubi, 2017;Do et al, 2020). Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF.…”
Section: Introductionmentioning
confidence: 57%
“…Some previous studies present that among the crucial factors affecting NPL are economic growth, which negatively correlates with the NPL and NPF. Similar studies have found that macroeconomic factors have a significant relationship with NPL and NPF (Alzoubi, 2017;Do et al, 2020). Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF.…”
Section: Introductionmentioning
confidence: 57%
“…The study recommended that Islamic bank have to improve their Profits and Losses Sharing (PLS) investment in order to reduce their liquidity risk and to reinforce Islamic instruments of liquidity risk management. Alzoubi (2017) has analysed the determinants of liquidity risk in a study of 42 Islamic banks from 15 countries for a period from 2007 to 2014. The author applied panel data analysis to test the independents variables impact to liquidity risk that measured by total deposits to total assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we expect that the higher this ratio the less liquidity risk exposure in the bank. This ratio applied by Alzoubi (2017).…”
Section: Characteristics Of Variables and The Modelmentioning
confidence: 99%
“…Kemudian penelitian yang dilakukan (Masruroh, 2018) (Sulistia, 2018). Hasil penelitian ini mendukung penelitian yang dilakukan oleh (Alzoubi, 2017), (Bani & Yaya, 2015), (Effendi & Disman, 2017), (Chowdhury et al, 2019), (Ahmed & Ahmed, 2011)…”
Section: Penelitian Ini Membuktikan Bahwaunclassified